Power Amplifier Modeling and EVM Measurement Technique - Ben, Ooi Zee Min (2010)
This work will contribute to the area of nonlinear behavioral modeling of RF power amplifier for computer aided design and to the development of alternative methods toward EVM simulation and measurement.